Rotationally induced luminescence of nanoclusters immersed in superfluid helium - McColgan, P.T.; Sheludiakov, S.; Rentzepis, P.M.; Lee, D.M.; Khmelenko, V.V. (Физика низких температур, 2019)
We studied the influence of rotation speed of a beaker containing superfluid helium (He II) on the intensity of
luminescence of collections of nanoclusters immersed in He II. We observed an increase in the α-group emission
of nitrogen atoms (²D→⁴S transition) in nanoclusters which correlated with the increasing of rotational speed of
the beaker. Increasing luminescence was also observed by increasing the concentration of molecular nitrogen in
the nitrogen-helium gas mixtures used for the formation of the molecular nitrogen nanoclusters. We suggest that
this effect is caused by the change of the density of quantum vortices in He II initiated by variation of rotational
speed of the beaker. When the density of the vortices is increased, the probability for the nanoclusters to become
trapped in the vortex cores is also increased. The collisions in the vortex cores of trapped nanoclusters with nitrogen atoms stabilized mostly on the surfaces of the nanoclusters initiate the recombination of nitrogen atoms
resulting in luminescence. Досліджено вплив швидкості обертання склянки з надплинним гелієм (He II) на інтенсивність люмінесценції нанокластерів, які знаходяться всередині He II. Спостерігається
збільшення емісії α-групи атомів азоту (перехід ²D→⁴S) в
нанокластерах, яке корелювало зі збільшенням швидкості обертання склянки. Збільшення люмінесценції також спостерігалося
при збільшенні вмісту молекулярного азоту в азотно-гелієвій
газовій суміші, яку використовували для отримання нанокластерів молекулярного азоту. Ми припускаємо, що цей ефект
пов'язаний зі зміною щільності квантових вихорів в He II при
зміні швидкості обертання склянки. При збільшенні щільності
вихорів ймовірність захоплення нанокластеров в серцевинах
вихорів також підвищується. Усередині серцевин вихорів
відбувається зіткнення нанокластерів, внаслідок цього відбувається рекомбінація атомів азоту, що знаходяться на
поверхні нанокластерів, та їх люмінесценція. Исследовано влияние скорости вращения стакана со
сверхтекучим гелием (He II) на интенсивность люминесценции нанокластеров, находящихся внутри He II. Наблюдается
увеличение эмиссии α-группы атомов азота (переход ²D→⁴S)
в нанокластерах, которое коррелировало с увеличением скорости вращения стакана. Увеличение люминесценции также
наблюдалось при повышении содержания молекулярного
азота в азотно-гелиевой газовой смеси, используемой для
получения нанокластеров молекулярного азота. Мы предполагаем, что этот эффект связан с изменением плотности
квантовых вихрей в He II при изменении скорости вращения
стакана. При увеличении плотности вихрей вероятность захвата нанокластеров в сердцевинах вихрей также увеличивается. Внутри сердцевин вихрей происходит столкновение
нанокластеров, в результате которого происходит рекомбинация атомов азота, находящихся на поверхности нанокластеров, и их люминесценция.